Tinjauan Yuridis terhadap Kuasa yang Diberikan WNI kepada WNA untuk Mengalihkan Hak atas Tanah - A.A. Gede Cahya Pratama; I Nyoman Sumardika; I Wayan Arthanaya (Warmadewa Press, 2020)
A representative institution takes possession of a unique characteristic since the legal consequences born by both the principal and the attorney in fact are divergent. This is why the attorney as a part of a representative legal institution in practice causes many problems. In terms of granting the attorney, what is done in practice is in opposition to the ordinary granting of power, in that, the intended attorney is given by an Indonesian citizen (hereinafter is WNI) to a foreign citizen (hereinafter is WNA) to transfer the title to land of an Indonesian citizen to the party who wants to purchase the land that has been controlled. In the study, there are two legal issues examined, the form of granting the attorney by Indonesian citizens to foreign nationals regarding the transfer of title to land and the legal consequences arising from the granting of the attorney. The results indicate that the granting of attorney is not in the form of a full action against what is granted to the attorney in fact by principal, but an act of attorney which is only an extension of the hand of the principal over what the principal wants in accordance with Article 1792 BW. The legal consequences arising from granting attorney from Indonesian citizens to foreign nationals are in full responsibility of the principal within predetermined limits. Every citizen needs pay serious attention to realising in the real actions the determination of not to transfer their ownership rights of lands to other parties outside of Indonesian citizens. This can be supported by the conducting a number of scientific studies related to the ownership of lands, including those related to anticipatory efforts towards it.